An LC–MS/MS assay for the quantitative determination of 2‐pyridyl acetic acid, a major metabolite and key surrogate for betahistine, using low‐volume human K2EDTA plasma. (10th August 2016) - Soni, Krunal; Bhatt, Chandrakant; Singh, Kanchan; Bhuvaneshwari, P.C.; Jha, Anil; Patel, Palak; Patel, Harilal; Srinivas, Nuggehally R.
Abstract: Betahistine is widely used for the treatment of vertigo. Owing to first‐pass metabolism, 2‐pyridyl acetic acid (2PAA, major metabolite of betahistine) was considered as surrogate for quantitation. A specific and sensitive LC–MS/MS method was developed and validated for quantitation of 2PAA using turbo‐ion spray in a positive ion mode. A solid‐phase extraction was employed for the extraction of 2PAA and 2PAA d6 (IS) from human plasma. Chromatographic separation of analytes was achieved using an ACE CN, 5 μm (50 × 4.6 mm) column with a gradient mobile phase comprising acetonitrile–methanol (90:10% v /v) and 0.7% v/v formic acid in 0.5 mm ammonium trifluoroacetate in purified water (100% v/v). The retention times of 1.15 and 1.17 min for 2PAA and internal standard, respectively, were achieved. Quantitation of 2PAA and internal standard was achieved by monitoring multiple reaction monitoring transition pairs ( m / z 138.1 to m / z 92.0 and m / z 142.1 to m / z 96.1, respectively). The developed method was validated for various parameters. The calibration curves of 2PAA showed linearity from 5.0 to 1500 ng/mL, with a lower limit of quantitation of 5.0 ng/mL. The bias and precision for inter‐ and intra‐batch assays were <10%. The developed method was used to support clinical sample analysis.